A THEORETICAL INTERPRETATION OF MU-SR EXPERIMENTS TO MEASURE THE LONDON PENETRATION DEPTH IN ANISOTROPIC TYPE-II SUPERCONDUCTORS - Barford, W; Gunn, J (1988)
We calculate the London penetration depth as a function of the angle between the c axis and the direction of the vortex flux lattice for anisotropic type II superconductors. We use this result to calculate the effective penetration depth for a polycrystalline sample in the intermediate field region as would be measured by a μ SR experiment. We find that for an anisotropy ratio of 10 λeff=1.5 λ1 (where λ1 is the smaller principal penetration depth). For lower fields (near Hc1) 1.5 λ1 ≤λeff<√λ1λ3. λ3 is the larger penetration depth.